Safety and security in Abu Dhabi: The impact of policing on public perceptions - Sebire, Jacqueline (International journal of law, crime and justice, 2025)
The findings from public surveys conducted in Abu Dhabi since 2015 have consistently found individuals' perceptions of ‘feelings of safety’ scored over 90%. This study investigates the factors that contribute to the public's perception of safety in public spaces using the Emirate's Community Safety Survey. Correlative analysis identified that confidence in Abu Dhabi Police's plans and procedures, responses to traffic-related incidents, and emergency responses were influential, with moderate correlation values above 0.30. Inferential analysis revealed that confidence in and satisfaction with the Abu Dhabi Police service, along with confidence in their ability to set plans and procedures, played an important role in enhancing public safety perceptions. The ordinal regression model, with a predictive accuracy of 86.65%, could be used to accurately predict the levels of safety in Abu Dhabi. These findings suggest strategic areas for police to focus on when improving public safety perceptions.